2009
DOI: 10.1111/j.1460-9592.2009.02980.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative opioid dosing in children with and without cerebral palsy

Abstract: Similar to prior research on children with cognitive impairment, a reduction in intraoperative opioid dosing was found in children with CP. Given the discrepant doses of intraoperative opioid between groups, it is unclear whether children with CP are at any greater risk for untoward opioid-related events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
(14 reference statements)
0
17
0
Order By: Relevance
“…This could be seen as an improvement, because a previous survey found that 89% of the physicians have a tendency to prescribe subtherapeutic doses of opioids (2). In addition, two other studies report lower doses of intraoperative opioids in intellectually disabled children (16,17). One previous study by Malviya et al.…”
Section: Discussionmentioning
confidence: 99%
“…This could be seen as an improvement, because a previous survey found that 89% of the physicians have a tendency to prescribe subtherapeutic doses of opioids (2). In addition, two other studies report lower doses of intraoperative opioids in intellectually disabled children (16,17). One previous study by Malviya et al.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid dosing is commonly reduced in children with cognitive impairment (87), an observation supported by lower BIS scores in this cohort when given doses similar to healthy comparators (88). Behavioral predispositions such as preoperative anxiety also increases propofol induction dose (89).…”
Section: Pharmacodynamic Variabilitymentioning
confidence: 63%
“…Even when the pain is acknowledged, this population receives fewer analgesics than the general population (51, 52). Pain is a subjective and complex phenomenon; self-assessment may be the best defense against misconceptions.…”
Section: Resultsmentioning
confidence: 99%